Asepsis in Operative Dentistry and Endodontics - Priyanka Sriraman; Prasanna Neelakantan (Intelektual Pustaka Media Utama, 2014)
Operative (Conservative) dentistry and endodontics are specialties of dentistry where the operator is exposed to various infectious agents either via contact with infected tissues, fluids or aerosol. The potential for cross infection to happen at the dental office is great and every dentist must have a thorough knowledge of the concepts of sterilization and disinfection. Disposables should be used wherever possible. Furthermore, the water supply to the dental chair units and water outlets can house biofilms of microbes and should be considered as possible sources of infection. This review discusses the importance of following strict aseptic protocols from the perspective of operative dentistry and endodontics.